Comparative assessment of macroprudential policies - Bruno, Valentina; Shim, Ilhyock; Shin, Hyun Song (Journal of Financial Stability, 2017)
This paper provides a comparative assessment of the effectiveness of macroprudential policies in 12 Asia-Pacific economies over 2004–2013, using databases of domestic macroprudential policies and capital flow management (CFM) policies. We find that banking sector CFM policies and bond market CFM policies are effective in slowing down banking inflows and bond inflows, respectively. We also find some evidence of spillover effects of these policies. Finally, regarding the interaction of monetary policy and macroprudential policies, our empirical findings suggest that macroprudential policies are more successful when they complement monetary policy by reinforcing monetary tightening, than when they act in opposite directions.